2019
DOI: 10.1021/acs.inorgchem.8b03424
|View full text |Cite
|
Sign up to set email alerts
|

[C6N2H18][SbI5]: A Lead-free Hybrid Halide Semiconductor with Exceptional Dielectric Relaxation

Abstract: C 6 N 2 H 18 ][SbI 5 ] (1), a novel metal halide semiconductor with dielectric relaxation behavior, has been successfully synthesized, in which the cavities between the one-dimensional [SbI 5 ] n 2− polyanions are occupied by 2-methyl-1,5pentanediammonium (2-MPDA) cations. 1 undergoes a reversible solid-state phase transition at T C = 192.7 K and shows a step-like dielectric anomaly. Interestingly, above T C , distinct dielectric dispersion in a wide temperature range is also witnessed. Remarkably, the solid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 66 publications
3
27
0
Order By: Relevance
“…[13b,15] This single-stranded structure formed by corner-sharing halides is also present in other reported OIMHs. [16,17] The structural stability was studied by collecting powder X-ray diffraction (PXRD) patterns of fresh samples and samples exposed to air for 6 months. Accordingly, comparing the PXRD before and after air exposure, no changes were observed, and all of these can be well refined by the Rietveld method based on the structural model obtained by single crystal X-ray diffraction (Figure 2 samples before and after air exposure, which indicates that water molecules did not penetrate the crystal lattice, verifying their non-hygroscopicity (Table S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[13b,15] This single-stranded structure formed by corner-sharing halides is also present in other reported OIMHs. [16,17] The structural stability was studied by collecting powder X-ray diffraction (PXRD) patterns of fresh samples and samples exposed to air for 6 months. Accordingly, comparing the PXRD before and after air exposure, no changes were observed, and all of these can be well refined by the Rietveld method based on the structural model obtained by single crystal X-ray diffraction (Figure 2 samples before and after air exposure, which indicates that water molecules did not penetrate the crystal lattice, verifying their non-hygroscopicity (Table S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…− octahedra [21,[36][37][38], which decreases the carrier transport within the (−120) plane of the Cs 3 Bi 2 Br 9 SC. Shi et al [39] reported that the exciton binding energies (E b ) of Cs 3 Bi 2 Br 9 and Cs 2 AgBiBr 6 were 322 and 85 meV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…6a , compound 1 not only has switchable thermodynamic properties, but also interesting photoluminescence properties. 47 At 538 nm excitation wavelength, a strong photoluminescence (PL) emission corresponding to yellow emission was observed at 574 nm. At the same time, in order to understand the effect of a structural phase transition on the photoluminescence characteristics, we also carried out temperature-dependent photoluminescence (PL) measurement, where the measurement temperature range was 320–420 K, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%